Design and fabrication of rice washing machine / Muhammad Luqman Arif Mohd Azmi - Mohd Azmi, Muhammad Luqman Arif (2023)
Rice is a daily staple food and the country's primary source of calories. As a result, rice is in great demand. The automated system must be given priority to meet the demand. The issue is that hand-washing rice grains in large quantities is time-consuming. As a result of this invention, caterers will be able to wash their large quantities of rice grains more efficiently and with less energy. The problem is that washing rice grains in large quantities by hand is laborious. As a result of this project, the caterers will be able to wash their vast numbers of rice grains with little energy in a short time. Because this machine works with rice, stainless steel has been used for the spinner. This project is expected to be cheap and durable. In conclusion, this machine will benefit caterers, college students, and lower-income families at an affordable price.